Polyphonic Theory and Contemporary Literary Practices - M.-Pierrette Malcuzynski (Studies in 20th & 21st Century Literature, 1984)
This paper briefly explores some of the ways in which Mikhail Bakhtin reaffirms the principle of the non-identity yet inseparability of theory and practice in literary criticism. The lesson is one which stresses the need to disentangle the critical discourse from idealistic theoretical issues and engage in a materialist practice of criticism. If polyphonical dialogism (especially with respect to contemporary polyphony) is not to be confused with dialectics, then the most urgent and perhaps the most difficult task for the critic facing a polyphonic narrative is to negotiate the text in terms of the socio-historical actuality of the transformation which that text proposes. An analysis of D.M. Thomas' The White Hotel illustrates the ideological problems that arise when the operative system of the polyphonical narrative structure is stretched to the limit—as is moreover the case with many contemporary novels. And if the critic is to engage in a form of praxis, then he has to re-dialecticize the political (unconscious?) consciousness, in short, to politicize and not merely theorize its anticipated actualization.
Keywords: Polyphonic Theory; Contemporary literature; Mikhail Bakhtin; non-identity; theory of the non-identity; identity; materialist; materialist criticism; polyphonic dialogism; polyphonic narrative; socio-history; D.M. Thomas; The White Hotel; political consciousness; English literature